2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649847
|View full text |Cite
|
Sign up to set email alerts
|

Automatic breast cancer grading of histopathological images

Abstract: Breast cancer grading of histopathological images is the standard clinical practice for the diagnosis and prognosis of breast cancer development. In a large hospital, a pathologist typically handles 100 grading cases per day, each consisting of about 2000 image frames. It is, therefore, a very tedious and time-consuming task. This paper proposes a method for automatic computer grading to assist pathologists by providing second opinions and reducing their workload. It combines the three criteria in the Nottingh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 12 publications
0
53
0
2
Order By: Relevance
“…Secondly several structures, besides tubules, also contain lumen, i.e., blood vessels and Scientific RepoRts | 6:32706 | DOI: 10.1038/srep32706 other types of glands. Morphological operators have been used to connect proximal cancerous cells and generate blob structures 9 . These blobs were identified as tubules when they were found to be surrounding a white space or lumen.…”
mentioning
confidence: 99%
“…Secondly several structures, besides tubules, also contain lumen, i.e., blood vessels and Scientific RepoRts | 6:32706 | DOI: 10.1038/srep32706 other types of glands. Morphological operators have been used to connect proximal cancerous cells and generate blob structures 9 . These blobs were identified as tubules when they were found to be surrounding a white space or lumen.…”
mentioning
confidence: 99%
“…83 Several algorithms have been proposed to segment tubules in BC H&E images. However, a morphological operation that proposed earlier time 84 showed false-positive results. Adipose tissue was also regarded as a tubule in that research, whereas Naik et al 85 first identified lumen, epithelial cytoplasm, and nuclei using a Bayesian classifier.…”
Section: Image Preprocessingmentioning
confidence: 99%
“…This can be lesser representative than having a score established according to the whole preparation which was of course too tedious for pathologists under a classical microscope until now. With the advent of fast whole slide image scanners, it is now possible [6]. Our study drives towards this direction.…”
Section: Visual Analysis Processmentioning
confidence: 99%